REAGENT METHOD OF DIVISION OF THE MULTILAYERED PACKING MATERIALS, APPLIED IN CIVIL AVIATION, FOR THEIR THE SUBSEQUENT UTILIZATION - N. E. Nikolaykina; E. Yu. Starkov (Научный вестник МГТУ ГА, 2016)
The article deals with the actual problem of utilization of the solid waste resulting from activity of civil aviation as it is demanded by a state policy in the sphere of the Russian Federation transport. Existence of a significant amount of waste of a different classes of dauger allows to consider this problem in a complex with an individual approach to each class. Use of chemical reagents (acetic and (or) nitric acids) will allow to solve effectively the problem connected with utilization of the food multilayered packing materials accumulated in airports food services as well as a problem of processing similar solid waste in case of aviation incidents.The technology of process of division, the modes of carrying out the process are recommended. Comparison of carrying out process efficiency for various reagents when changing the technological parameters is given. Division of layers of multilayered materials allows to use the technologies which are already approved in the industry for their utilization. It is shown that it will allow to solve the problem connected with the accumulation of food multilayered packing materials more effectively in civil aviation.